2tan^-1(tanx/2×tan(π/4-y/2))=tan^-1(sinx×siny/cosx+cosy)

1 answer

You sure there are no typos? I suspect you want

(sinx+siny)/(cosx+cosy)

Anyway, you can get things a bit simpler by taking the tan of both sides, since

tan(arctan(x)) = x

also,

tan(x/2) = (1-cosx)/sinx
Similar Questions
    1. answers icon 1 answer
  1. Simplify #3:[cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] =
    1. answers icon 1 answer
  2. Trigonometric IdentitiesProve: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx +
    1. answers icon 0 answers
    1. answers icon 5 answers
more similar questions